提高滚子的抗冲击性能研究 - 尹德兵; 王怀宇; 程亚兵; 赵建祥 (Jixie chuandong)
Improving resisting fatigue lifetime method of cold welding roller is studied.Test results show that hole extruding of six-position replacing five-position cold welding machine,the inner stress of post-molding roller is decreased,and the steps and mangle pit of roller wall are eliminated.After heat treatment,resisting impact fatigue lifetime of roller is improved obviously.